2015
DOI: 10.1089/ten.tea.2014.0537
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation Effectiveness of Induced Pluripotent Stem Cells Is Improved by a Fibrinogen Biomatrix in an Experimental Model of Ischemic Heart Failure

Abstract: The fibrinogen biomatrix improved cardiac iPSc retention, sustaining functional improvement and cellular refill of infarcted myocardium. Therefore, fibrinogen can be considered an ideal biological scaffold for intramyocardial stem cell transplantations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A commonality of most myocardial cell therapy studies is the application of aqueous injection media for cell transfer (12,36). Previously, using fluorescent microspheres ass cell surrogate, we showed that aqueous injections are marked by early injection loss and redistribution from the injection site via venous drainage to the lung (37). Therefore, for this study, fibrinogen as injection vehicle was chosen to retain injected stem cells in the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A commonality of most myocardial cell therapy studies is the application of aqueous injection media for cell transfer (12,36). Previously, using fluorescent microspheres ass cell surrogate, we showed that aqueous injections are marked by early injection loss and redistribution from the injection site via venous drainage to the lung (37). Therefore, for this study, fibrinogen as injection vehicle was chosen to retain injected stem cells in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed that ineffective cell transfer (9), retention (9), engraftment (10,11), and survival (12)(13)(14) are major hurdles for myocardial regeneration by stem cells and might obscure therapy effectiveness. Thus, independently of which stem cell type is chosen, the optimization of these factors is needed to improve stem cell therapy (15,16). For this purpose, noninvasive methods that allow assessing cell viability in vivo after intramyocardial transplantation are indispensable (15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Also, they promote migration of endothelial cells and smooth muscle cells and, simultaneously, confer CMs protection from apoptosis. In addition, these materials have low immunogenicity and have anti-inflammatory and pro-angiogenic properties [17,18,20,37,50,53,67,107,108,112,115]. This explains why delivery of stem cells in scaffolds has higher benefits to those delivered in aqueous or in culture media, with regard to cell retention and proliferation as well as structural and functional myocardial recovery.…”
Section: Combination Of Different Stem Cellsmentioning
confidence: 99%
“…However, fibrin is more viscous than fibrinogen and may, in fact, challenge cell injection and cell nutrition. That is why Rojas et al [107] preferred to imprison iPSC in a fibrinogen matrix. Similarly, animals treated with iPSC and fibrinogen displayed improved LVEF in comparison to those treated with iPSC and medium.…”
Section: Combination Of Different Stem Cellsmentioning
confidence: 99%
“…There are different types of stem cells such as embryonic stem cells, adult stem cells, and induced pluripotent stem cells for treatment of CVDs (Table 1). Previous studies have demonstrated therapeutic effects of ESCs differentiated into cardiomyocytes [17] and endothelial cells [18] for myocardial infarction, umbilical-cord-blood-derived MSCs for dilated cardiomyopathy [19], bone-marrow-derived-MSCs for cellular cardiomyoplasty [20], and iPSCs [21] and iPSCs-derived cardiovascular progenitor cells [22], endothelial progenitor cells (EPCs) [23], and cardiac stem cells [24] for myocardial infarction.…”
Section: Cardiovascular Diseases and Stem Cellsmentioning
confidence: 99%